From Pituitary Adenoma to Pituitary Neuroendocrine Tumors: How Molecular Pathways may Impact the Therapeutic Management? - Chiloiro, Sabrina; De Marinis, Laura (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
The classification of adeno-pituitary tumor was deeply revised over the last 20 years, in order to better describe the variable and complex biological and clinical behavior of these neoplasia and to identify prognostic markers of aggressiveness and poor prognosis. Recently, the International Pituitary Pathology Club proposed to replace the term “pituitary adenoma” with “pituitary neuroendocrine tumour” (PitNET), to reflect similarities of adeno-pituitary tumours with neuroendocrine neoplasia of other organs, underling better the variable behaviour of adeno-pituitary neoplasia. A definitive consensus was not reached on this issue. In this review, we will describe how molecular and biological marker can predict aggressiveness of PitNETs and impact on therapeutic management of PitNETs.
Keywords: gonadotropinoma